Road Construction Delay Risk Identification Based On The Relative Importance Index Method - Fadlansyah, Heldifha; Sandhyavitri, Ari; Iriana, Rian Trikomara (Jurnal Rekayasa Sipil, 2024)
The Widening Project to Add Lanes to the Siak IV Pekanbaru Access Road is one of the road construction projects that experienced a delay of 27.791% of the planned schedule. The delay requires risk identification and assessment as an initial form of risk management. This study aims to identify the causal factors of the risk of delays during the construction period by using one of the risk identification methods, namely the Relative Importance Index (RII) method with a Likert Scale, the influence from no effect or 1 to very influential or 5. Out of 63 risk variables delays obtained 11 valid risks by the validity test with the Item-Level Content Validity Index (I-CVI). Therefore, using the RII method, a list of risks from the highest impact to project delay was obtained which was equipment with a value of 1.00 and the last was rain with a value of 0.25. To prove the risk factors, The Critical Path Method (CPM) was then applied, revealing 26 activities categorized as critical paths in 9 main works of the project. In conclusion, the risks were proved which caused the project delay and impacted the critical path in progress of the project.